Targeting phosphoglycerate dehydrogenase enzyme using ginger compounds to suppress thyroid cancer progression - Rahman, Faris I.; Zulfa, Putri O.; Beočanin, Anđelija; Faisal, Ibraheem M.; Louca, Nicolas; Carstoiu, Maria I.; Zufry, Hendra (Narra Sains Indonesia, 2024)
Recent studies have recognized the potential of inhibiting phosphoglycerate dehydrogenase (PHGDH) enzyme as a therapeutic strategy for treating papillary thyroid cancer. However, research on the efficacy of herbal compounds in inhibiting the PHGDH enzyme that have been reported to possess anticancer activities, including those found in ginger (Zingiber officinale), remains limited. The aim of this study was to examine the potential of ginger compounds in inhibiting PHGDH enzyme and to identify its potential use in the treatment of papillary thyroid cancer. The study employed computational methods to identify ginger-derived compounds that inhibit the PHGDH and impede papillary thyroid cancer progression. Crystallized protein structures were obtained from the Protein Data Bank, and Discovery Studio software was utilized to remove water molecules, double chains, and ligands. The receptor was modified by adding polar hydrogen, and AutodockTools4 software was employed to establish an accurate binding site based on the position of the previous ligand. Molecular docking experiments were conducted with 125 ginger-derived phytochemicals retrieved from the PubChem database. The results revealed nine active compounds found in ginger (galanolactone, myricetin, quercetin, cyanin, kaempferol, chlorogenic acid, delphinidin, alpha-cadinol, and curcumin) with strong binding affinities to PHGDH (minimum score threshold <-7 kcal/mol), indicating their potential for drug development. Galanolactone, myricetin, and quercetin were the top three compounds with the strongest binding affinity (-8.2, -7.9, and -7.9 kcal/mol, respectively), involving multiple bonds in the ligand-protein complex interaction. Notably, myricetin and quercetin formed three hydrogen bonds each, contributing to strong and stable bonds with the pocket region of PHGDH. In conclusion, ginger-derived compounds show promise in inhibiting PHGDH for the treatment of papillary thyroid cancer. However, further research is needed to validate the efficacy of these compounds and their interactions with the PHGDH in the context of thyroid cancer therapy.